Trade Policy and Food Security : Improving Access to Food in Developing Countries in the Wake of High World Prices - Gillson, Ian; Fouad, Amir (Washington, DC: World Bank, 2014)
Based on forecasts of global population growth, food security will remain an important economic development issue over the next several decades. In addition, real food prices have risen in recent years after decades of decline, bringing the issue of food security even further into the public spotlight. However, there is no global food shortage: the problem is one of moving food, often across borders, from surplus production areas to deficit ones at prices that low-income consumers in developing countries can afford.